Letter (copy) : Basque seamen - Tewson, Vincent
025a-0078-001 International HVT/AC/469 18th September, 1939. Señor Victor Saez, Basque Social Secretariat, 14, Eccleston Sq., S.W.1. Dear Sir, BASQUE SEAMEN I am very pleased to have your letter of 14th September, in which you make suggestions with respect to possible avenues of employment of the Basque seamen in our care in ports in this country. Señor Lizaso has already had a word with me on the telephone with regard to this matter, and you may rest assured that the contents of your letter will be kept very closely in mind. Please allow me to thank you, and through you your friends, for the very kind offer of help, of which I am sure advantage will be taken when circumstances permit. Yours faithfully, Assistant Secretary. 292/946/25a/78